Design metrics and Performance Exploration of Asymmetric HBLLC converter - Jenifer.A, Dr.Y.Sukhi, Anil Kumar N (Mathematical Statistician and Engineering Applications, 2022)
This study presents an asymmetric half-bridge (HB) resonant DC-DC converter. This converter is derived by integrating a buck–boost, on the input side with the HBLLC resonant converter. The buck boost converter on the line side gives the supply voltage to the secondary which boosts it hence the conduction losses is less. An asymmetric pulse width modulation (PWM) control is used to get broad range of input. This converter gives high efficiency, less conduction losses and it is proved by testing the system in Matlab simulation package.